2007
DOI: 10.1136/bjo.2006.111757
|View full text |Cite
|
Sign up to set email alerts
|

The socioeconomic impact among Egyptian glaucoma patients

Abstract: Background/aim: To evaluate the economic burden of intraocular pressure (IOP)-lowering medications on Egyptian patients with glaucoma, in addition to studying the social grounds of glaucoma education. Methods: In a cross-sectional observational study, the clinical and socioeconomic data were collected from 68 glaucomatous patients who were attending the outpatient clinics of Cairo University Hospital, through interviews, questionnaires, and clinical examinations. Results: Patients had a mean IOP of 22.9 mm Hg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…This is because the patient usually overestimates his compliance level and usually sticks to the prescribed regimen two to three days prior to his next follow-up visit, so that even intraocular pressure cannot be considered a clue to patient adherence [ 9 , 10 ]. In developing countries where socioeconomic standards are poor and the patients are not well-educated, if educated at all, it is even more challenging to measure patient compliance [ 11 ]. In Egypt, electronic dose monitors are not readily available, and pharmacy records are always missing or difficult to obtain because medical insurance does not cover most individuals, so the patient can buy his medication from whichever pharmacy he chooses and does not have to stick to certain pharmacies related to his insurance provider.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the patient usually overestimates his compliance level and usually sticks to the prescribed regimen two to three days prior to his next follow-up visit, so that even intraocular pressure cannot be considered a clue to patient adherence [ 9 , 10 ]. In developing countries where socioeconomic standards are poor and the patients are not well-educated, if educated at all, it is even more challenging to measure patient compliance [ 11 ]. In Egypt, electronic dose monitors are not readily available, and pharmacy records are always missing or difficult to obtain because medical insurance does not cover most individuals, so the patient can buy his medication from whichever pharmacy he chooses and does not have to stick to certain pharmacies related to his insurance provider.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma is called the -sneak thief‖ of sight because it often goes undetected in its earliest stages ( Figure 1). About 50% of individuals in North America with glaucoma are not aware of it, and the problem is worse in less medically advanced portions of the world [4][5] and about 40% of the Egyptian population does not know that glaucoma causes blindness [6]. The primary source of knowledge in Egyptian population about glaucoma data for patients was mainly the ophthalmologists, followed by friends and relatives.…”
Section: Fig1 Normal Eye and Eye With Glaucomamentioning
confidence: 99%
“…The primary source of knowledge in Egyptian population about glaucoma data for patients was mainly the ophthalmologists, followed by friends and relatives. Newspapers, TV and non-ophthalmic doctors played a smaller role, whereas radio, movies, and the Internet appeared to play no role at all (Table 1) [6].…”
Section: Fig1 Normal Eye and Eye With Glaucomamentioning
confidence: 99%
“…Recent medications which reduce IOP in patients with POAG are effective in delaying or preventing the onset of POAG. However, these medications may cause ocular irritation and other side effects in addition to the socioeconomic impact among patients with glaucoma [8][9][10][11]. Several studies demonstrated the effect of different types of exercises, including aerobic and resisted exercise for short time on IOP in normal population and patients with POAG [12,13].…”
Section: Introductionmentioning
confidence: 99%